Basics of Shariain poetry of akyns and zhyray (Eurasian Journal of Philology Science and Education, 2018)
The disclosure of the great goal of the creator of the world, and zhyrau akyns society ascribe todeep clean and the origins of Islam. These sources come from the Koran, have strong foundation in thelast Messenger of Allah Hadith of the Prophet Muhammad (ғ.s.) and in the writings of Islamic scholarsand the heirs of the medieval literary tradition.These motifs Creation heard from the Arch to Atyrau, andthrough them representatives of the traditional art of singing schools ascribe his audience to the laws ofthe universe, urging them to take as a perfect example.His article discusses the philosophical ideas about the the duty of Muslims, prevailing in songs-tolgauakyns zhyrau and early twentieth century. Along with the normal development of human history, andzhyrau akyns urged his listeners to follow the example of the Muslim duty. The great mission of manbefore God – the desire to know the existence of the Creator and the Maker of it.